The influence of training loads of technical and tactical training on the cardiovascular system of tennis players 10-12 years - I.I. Yevtyfiieva; V.A. Korobeinik; A.O. Kolisnychenko (H.S. Skovoroda Kharkiv National Pedagogical University, 2020)
Purpose: theoretical and experimental substantiation of the use of rational technique of technical and tactical training of tennis players of 10-12 years and determination of the influence of training and competitive loads on the body of athletes. Material and methods. 16 tennis players aged 10-12 years from the Polytechnic Sports Club of the National Technical University "Kharkiv Polytechnic Institute" took part in the study, 8 athletes were included in the experimental group and 8 in the control group. The experiment was conducted for three months in the preparatory period at the stage of basic preparation of the second year of study. The experimental group trained in the advanced technique of tactical training on the block system, using heart rate monitors and video devices. At the beginning and at the end of the experiment, control competitions were conducted and heart rate was recorded at the beginning and end of each performed series of beats and each exercise using a Polar heart rate monitor. Results. The proposed program of technical and tactical training of tennis players on the block system had a positive impact in the training and competitive process on the functional state of athletes. The analysis of the pulsegram of the athletes of the experimental group confirmed the assumption that the phase of working out of the systems of the organism under the influence of physical activity (from 4-5 minutes to 3-4 minutes) was reduced and that the phase of rapid recovery of the heart rate after removal of the load (from 3-4 minutes to 2- 3 minutes). The data obtained indicate the feasibility of using this technique for the preparation, control and evaluation of the competitive activity of tennis players 10-12 years. Conclusions. Positive influence of the application of the proposed method on the adaptive capacity of the athlete's body to the load has been determined. focus.